Subjective and objective in architectural modernity and post - Falah Jaber Jaber; Abbes Ali Hamza (Iraqi Journal of Architecture and Planning, 2018)
The architecture is the highest knowledge field and most reactive in human society where,human lives in this article includes sudjective and objective concepts and the relationship between them.Also, this shows the relation between these two concepts and the science of society, in order to show thebackground knowledge between those two concepts and reflection on architectural idea. This articleconcentrates to clear this dualism ingeneral architecture and in architectural modernity and post modernityin special aim, due to their relations. Each one completes the other concept in time also.